Perspectives on the Use of Coral Reef Restoration as a Strategy to Support and Improve Reef Ecosystem Services - Hein, Margaux Y.; Vardi, Tali; Shaver, Elizabeth C.; Pioch, Sylvain; Boström-Einarsson, Lisa; Ahmed, Mohamed; Grimsditch, Gabriel; McLeod, Ian M. (Frontiers in Marine Science, 2021)
In 2019, the United Nations Environment Assembly requested that the United Nations Environment Programme (UNEP) and the International Coral Reef Initiative (ICRI) define best practices for coral restoration. Guidelines led by the UNEP were prepared by a team of 20 experts in coral reef management, science, and policy to catalog the best-available knowledge in the field and provide realistic recommendations for the use of restoration as a reef management strategy. Here, we provide a synthesis of these guidelines. Specifically, we present (1) a case for the value of coral reef restoration in the face of increasing frequency and intensity of disturbances associated with climate change, (2) a set of recommendations for improving the use of coral reef restoration as a reef management strategy, tailored to goals and current methods. Coral reef restoration can be a useful tool to support resilience, especially at local scales where coral recruitment is limited, and disturbances can be mitigated. While there is limited evidence of long-term, ecologically relevant success of coral reef restoration efforts, ongoing investments in research and development are likely to improve the scale, and cost-efficiency of current methods. We conclude that coral reef restoration should not be seen as a “silver bullet” to address ecological decline and should be applied appropriately, with due diligence, and in concert with other broad reef resilience management strategies.